ChemInform Abstract: Broensted Acid Catalyzed Enantioselective Indole Aza‐Claisen Rearrangement Mediated by an Arene CH—O Interaction. Issue 16 (22nd April 2014) - Maity, Pradip; Pemberton, Ryan P.; Tantillo, Dean J.; Tambar, Uttam K.
Abstract The reaction tolerates a wide range of aromatic and heteroaromatic substituents at the allylic double bond and affords the products with high yields and enantioselectivities [cf.